Goal orientations and attitudes toward doping - Sas-Nowosielski, K.; Swiatkowska, L. (International Journal of Sports Medicine, 2008)
The aim of the study was to determine if there is a relationship between attitudes toward doping and achievement goal orientations of athletes. Questionnaires from 830 athletes (including 263 females) were obtained. Athletes declared moderately positive attitudes, with attitude toward anti-doping controls as the strongest and attitude toward sanctions as the weakest. Females declared significantly more favourable attitudes than males. With respect to the relationship between goal orientations and attitudes toward doping, it was found that athletes who were high task/low ego oriented declared the most favourable attitudes, while athletes who were low task/high ego oriented declared the least favourable attitudes. Multiple regression analyses confirmed that ego orientation was significantly negatively related to, and task orientation was significantly positively related to attitudes toward doping. It means that with the increase in task orientation, attitudes toward doping became more favourable. The opposite can be said about the increase in ego orientation. It could be argued then, that creating a motivational climate which promotes task orientation (mastery climate) may aid anti-doping efforts.